Multi-objective DG placement in radial distribution systems using the IbI logic algorithm - Saxena, Nitin; Pandit, M; Srivastava, L (Frontiers in Energy Research, 2024)
This paper presents a unique optimisation method based on the incomprehensible but intelligiblein-time (IbI) logic algorithm to optimally place dispersed generators in small, medium, large and very large (16-, 33-, 69-and 118-bus) radial distribution power networks to reduce power losses, the total operating cost and the voltage deviation and to improve the voltage level. Two types of multiple distributed generators (DGs) are employed in this study, one working at unity power factor and the other at 0.866 p.f. The IbI logic algorithm works on understanding logic that are currently not logic but would be so over time. The proposed approach was used to address a multi-objective multi DG placement problem. The results generated through this method were compared with those generated by other methods and were observed to be comparatively remarkable.